Effect of Clemastine on Neurophysiological Outcomes in an Ovine Model of Neonatal Hypoxic-Ischemic Encephalopathy - Jana Krystofova Mike; Yasmine White; Rachel S. Hutchings; Christian Vento; Janica Ha; Ariana Iranmahboub; Hadiya Manzoor; Anya Gunewardena; Cheryl Cheah; Aijun Wang; Brian D. Goudy; Satyan Lakshminrusimha; et al. (Children, 2023)
Originally approved by the U.S. Food and Drug Administration (FDA) for its antihistamine properties, clemastine can also promote white matter integrity and has shown promise in the treatment of demyelinating diseases such as multiple sclerosis. Here, we conducted an in-depth analysis of the feasibility, safety, and neuroprotective efficacy of clemastine administration in near-term lambs (n = 25, 141–143 days) following a global ischemic insult induced via an umbilical cord occlusion (UCO) model. Lambs were randomly assigned to receive clemastine or placebo postnatally, and outcomes were assessed over a six-day period. Clemastine administration was well tolerated. While treated lambs demonstrated improvements in inflammatory scores, their neurodevelopmental outcomes were unchanged.